2006
DOI: 10.1074/jbc.m602583200
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Hormones Cause Rapid c-Met Receptor Down-regulation by a Novel Mechanism Involving Clathrin-mediated Endocytosis and a Lysosome-dependent Mechanism

Abstract: The activated c-Met receptor has potent effects on normal tissues and tumors. c-Met levels are regulated by hepatocyte growth factor (HGF); however, it is unknown if they can be regulated by gastrointestinal (GI) hormones. c-Met is found in many GI tissues/tumors that possess GI hormone receptors. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 74 publications
2
18
0
Order By: Relevance
“…This model highlights the unique role of Src activation in contributing to the dual effects of CCK on Akt activation, in that its activation is essential for Akt stimulation with low doses of CCK, but is not important for the inhibitory effect of higher concentrations of CCK. In a recent study, these latter concentrations of CCK were reported to stimulate the degradation of c-Met in rat pancreatic acini [118]. In the present study, we report that similar concentrations of CCK inhibit PI3K and Akt activity in these cells, raising the possibility these effects could be caused by an effect on c-Met further downstream in the signal transduction pathway.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This model highlights the unique role of Src activation in contributing to the dual effects of CCK on Akt activation, in that its activation is essential for Akt stimulation with low doses of CCK, but is not important for the inhibitory effect of higher concentrations of CCK. In a recent study, these latter concentrations of CCK were reported to stimulate the degradation of c-Met in rat pancreatic acini [118]. In the present study, we report that similar concentrations of CCK inhibit PI3K and Akt activity in these cells, raising the possibility these effects could be caused by an effect on c-Met further downstream in the signal transduction pathway.…”
Section: Discussionsupporting
confidence: 63%
“…First, c-Met degradation after CCK follows a slow kinetic, starting at 10 minutes and reaching a maximum after 45 minutes [118], while Akt inhibition is maximal after only 2.5 minutes. Second, degradation of growth factor receptors after CCK is limited to c-Met, other growth factor receptors are not degraded [118]. As the latter effects are not regulated by c-Met, they cannot be mediated by CCK-induced c-Met degradation.…”
Section: Discussionmentioning
confidence: 99%
“…After treating isolated pancreatic acini with or without stimulants as indicated, cells were fixed, transferred to glass slides and blocked as previously described [28], then slides were incubated with a rabbit anti-pT538 PKCθ antibody and a mouse anti-cadherin antibody at a dilution of 1:500 overnight at 4 °C. Reactivity was demonstrated by incubation with an Alexa 488-conjugated anti-rabbit or with an Alexa 555-conjugated anti-mouse secondary antibody, respectively, at a dilution of 1:500 for 2 hours RT.…”
Section: Methodsmentioning
confidence: 99%
“…Negative controls consisted of replacement of primary antibody with an isotype-matched control. Slides were analyzed as previously reported [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Blocking the proteasomal or lysosomal degradation pathways individually was unable to greatly prevent 2BP-induced c-Met loss. Multiple reports detail the paradoxical effects these degradation pathways have on c-Met trafficking and stability [4648]. We find it likely that distinct intracellular pools of c-Met are degraded through different, possibly compensatory, pathways.…”
Section: Discussionmentioning
confidence: 65%